Industry Structure and Pricing over the Business Cycle - Yossi Spiegel; Konrad O. Stahl (Center for Economic Studies and ifo Institute (CESifo), 2014)
We consider the interaction between an incumbent firm and a potential entrant, and examine how this interaction is affected by demand fluctuations. Our model gives rise to procyclical entry, prices, and price-cost margins, although the average price in the market can be countercyclical if the entrant is a first mover, and capacity utilization can be either pro- or countercyclical if the incumbent is a first mover. Moreover, our results show that entry deterrence by the incumbent firm can either amplify or dampen the effect of demand fluctuations on prices, price-cost margins, and capacity utilization.
Keywords: D43; L41; 330; price competition; business cycle; entry; entry deterrence